Contributions to the cranial anatomy of the scincid Riopa sundevallii (A. Smith) - Ratte, T. W.(Theodor Wilhelm) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- Universiteit van Stellenbosch, 1969.